Climate and ET: do plant water requirements increase during a drought? - Swanson, Charles, author; Smith, David, author; Fipps, Guy, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
Municipalities, engineering consultants and State agencies use reference evapotranspiration (ETo) data (directly and indirectly) for long-term water planning, for designing hydraulic structures, and for establishing regulatory guidance and conservation programs intended to reduce water waste. The use of ETo data for agricultural and landscape irrigation scheduling is becoming more common in Texas as ETo-based controllers and automation technologies become more affordable. Until recently, most ETo data has been available as monthly values averaged over many years. Today, automated weather stations and irrigation controllers equipped with specialized instrumentation allow for real-time ETo measurements. With the expected rise in global warming and increased frequency of extreme climate variability in the coming decades, conservation and efficient use of water resources is essential and must make use of the most accurate and representative data available.
Irrigated agriculture responds to water use challenges
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.